Small task-oriented groups : a systems analysis : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Education at Massey University - Nolan, Clarence James Patrick; Harvey, Judith Ceridwen Irangani (Massey University, 1972)
Where two or more people are gathered together in order to engage in social interaction - there is a social system". (Anon.) The question of why it is that people come together in systems of interaction and how these systems persist as viable social arrangements is one which has been taken up by social philosophers and sociological theorists as far back as Hobbes. Subsequently Spencer, Durkheim, and such contemporary figures as Homans, Merton and Parsons have also taken issue with this problem. The present thesis shares a similar concern with the problem and derives its stimulus from the way in which sociologists have attempted to formulate adequate explanatory theories. The thesis exhibits a convergence in the interests of the two authors - on the one hand, an interest in the application of parsonian theory' to small group phenomena, and on the other, the use of 'systems theory' in the explanation of social interaction in educational settings. The specific focus of attention is on those groups which have the properties of being small and task-oriented. Such groups are ubiquitous in educational contexts. At the most general level the thesis uses Parsons' voluntaristic theory of social action as the frame of reference from which a theory of small task-oriented groups can be derived. The thesis is therefore an expedition into the realms of sociological theory and an exploration of the way in which parsons' theory in particular can be applied to an empirical situation. Elements of general systems theory have been employed to further limit the scope of the investigation by focussing only on the internal dynamic of small task-oriented groups, rather than the way in which they adapt to their surrounding environments, thus enabling such groups to be conceptualised as discrete social systems in their own right. [From Introduction]
Keywords: Teacher-student relationships; Social interaction; Small groups; Parsons, Talcott, 1902-1979